Pathological investigation, molecular characterization and first-time isolation of the predominant serotypes of fowl adenovirus (FAdV-D and E) from commercial poultry in Bangladesh - Sadekuzzaman, Mohammad; Miah, Md. Sojon; Parvin, Rokshana; Haque, Md. Enamul; Islam, Tanbin Rubaiya; Sigma, Sanzila Hossain; Hossain, Md. Golbar; Hayat, Sajedul; Hossain, Muhammad Tofazzal; Islam, Md. Alimul (Frontiers in Microbiology, 2024)
BackgroundFowl adenovirus (FAdV) is a globally distributed virus that inflicts significant economic losses on the poultry industry. The study aimed at pathological investigation, molecular characterization, isolation, and pathogenicity determination of FAdV from commercial poultry.MethodsA total of 86 liver samples were collected from 80 commercial chicken farms. All samples were examined for gross pathology; only liver samples were used for histopathology and virus detection by PCR. PCR-positive FAdV samples were used for isolation of virus in 10-day-old seronegative embryonated chicken eggs (ECEs) via chorioallantoic membrane (CAM). PCR confirmed virus isolates were sequenced for serotyping and phylogenetic analysis. Pathogenicity of the isolated FAdVs was assessed by oral, i.m., and i.p. routes of infection.ResultsThe study observed gross lesions including hydropericardium and enlarged, friable pale livers with ecchymotic hemorrhages. Histopathological analysis revealed hepatocytic necrosis with basophilic intranuclear inclusion bodies in liver tissues, and tubular necrosis, focal hemorrhages, and mononuclear cell infiltration in kidney tissues. Out of 86 liver samples analyzed, 40 were positive for FAdVs by PCR, and 22 were positive for virus isolation. One serotype was 11 and other 11 were 8b of FAdV and genetically close to Bangladesh, India, and Turkey isolates, according to hexon gene phylogenetic analysis. The pathogenicity test indicated that serotype 11 was more virulent than the serotype 8b.ConclusionThe study concluded that serotypes 11 and 8b of FAdVs are circulating simultaneously among commercial broiler and layer chickens, serotype 8b was found predominant one.